STATE SUPPORT AND ADAPTATION MEASURES OF AGRICULTURAL ENTERPRISES TO THE WTO CONDITIONS - Sergei V. Laptev; Evgeniya U. Korotaeva (Статистика и экономика)
Mechanism of financial support of agriculturalenterprises has various content and structure indifferent countries require different levels of cost andhas signiﬁcantly different effects application. One of the practical problems of economic science is thestudy of the mechanism of such a structure to support agricultural enterprises in Russia, where whenavailable resource constraints support orientationmanufacturers will increase proﬁts, increase their competitiveness, improve skills in the organizationof the reproductive process. The article deﬁ nes the principles of an effective mechanism of state supportof agricultural enterprises, the ways of solving thepractical mechanical problem.